APPLICATION OF SANCTIONS AGAIN ST NOT ARIES FOR VIOLATIONS OF THE CODE OF ETHICS RELATED TO UNFAIR COMPETITION - Muhammad Yusrizal (Inspiring Law Journal, 2025)
In carrying out their duties, notaries are required to work professionally and adhere tothe Notary Code of Ethics as stipulated in Law Number 2 of 2014, which amended LawNumber 30 of 2004 concerning the Notary Public (UUJN). The purpose of a notary isto provide legal services to the public, particularly in the deed-making process. Withthe increasing demand for legal services, the need for notary services is also increasing.Unhealthy competition among notaries can arise in various forms and ways. Like theUUJN, the Notary Code of Ethics also does not provide a clear explanation of the formsand methods of competition among notaries that can trigger such unhealthycompetition. Through several articles in the code of ethics, it is clear how the formsand methods of competition between notaries can lead to unhealthy business practices,when analyzed based on the Notary Code of Ethics. In general, unhealthy practicesamong notaries arise when individuals violate the Notary Law (UUJN) and the Codeof Ethics, such as setting lower fees than necessary, promoting themselves throughvarious media, or issuing deeds outside their designated work area. Ultimately, theseactions by notaries can create monopolies, violate professional norms, and potentiallyharm clients.